ANALISIS KESALAHAN SISWA BERDASARKAN KATEGORI NEWMAN DALAM MENYELESAIKAN SOAL MATERI FUNGSI - Iis Asriah Nurfalah; Chandra Novtiar; Euis Eti Rohaeti (IKIP Siliwangi, 2021)
This is a qualitative descriptive research with 20 students from class X PFPT-A SMKN 1 Cimahi as subjects. The objective is to find out the types of students’ errors when completing problem material functions referring to Newman error categories and their causes. The data analysis obtained from written tests and interviews. The data validity test was carried out by data reduction, data presentation, and data retrieval. The results showed that there were 4 types of errors made by students, namely errors of understanding by 16%, transformation errors by 15%, errors of process skills by 32%, and errors in writing answers by 1%. Moreover, the students’ error caused by several matters, such as the students not get used to the form of stories, unable to interpret the problem as a whole, the lack of practice in solving non-routine problems, and in a hurry when working on the questions.